PENGARUH BRAND IMAGE DAN PRODUCT DESIGN TERHADAP PURCHASE DECISION DAN REPURCHASE INTENTION PADA PRODUK SEPATU FUTSAL MEREK SPECS DI KOTA PEKANBARU - Mardio Alexi; Zulkarnain '; Tengku Firli Musfar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research is conducted to analyze the influence of Brand Image and Product design toward Purchase Decision and Repurchase Intention on customers of product futsal shoes brand Specs at Pekanbaru City . There are four latent variables in this research such as Brand Image (X1), Product Design (X1), Purchase Decision (Y1) and Repurchase Intention (Y2). The population of this study are all customers of product futsal shoes brand Specs at Pekanbaru City with a sample of 152 respondents were selected using accidental sampling method with criteria every player whose wear Specs futsal shoes at the fields. Data in this study are taken by giving them structural questionaires. Meanwhile, Path Analysis method are chosen for data analysis by SPSS version 21. The result of this research shows that Brand Image affect significantly towards Purchase Decision so the higher Brand Image is applied, the higher of Purchase Decision of Specs customers at Pekanbaru City, Product Design affect significantly towards Purchase Decision so the higher the Product Design then the higher Purchase Decision on Specs customers at Pekanbaru City, Brand Image affect significantly towards Repurchase Intention on Specs customers at Pekanbaru City. Product Design affect significantly towards Repurchase Intention on Specs Customers at Pekanbaru City. Purchase Decision proved to affect Repurchase Intention on Specs Customers at Pekanbaru City. Brand Image and Product Design affect significantly towards Repurchase Intention through Purchase Decision on Specs Customers at Pekanbaru City. Researchers suggest that Specs Company to keep and even improve the quality, realize the consumer desire and other factors that increase Purchase Decision dan Repurchase Intention customer.Keyword : Brand Image, Product Design, Purchase Decision, and Repurchase Intention